Stage collapse at the Indiana State Fair - Crandall, William, 1956-; Parnell, John A. (John Alan), 1964-; Spillan, John E. ([London] : SAGE, 2016)
The case concerns the dire weather conditions that caused problems to August's 2011 State Fair in Indiana during a concert. The Fair Commission was fined US$6,300 for failing to take into account the severe weather conditions and their potential impact on the safety of the concert fans.
Originally Published in: Crandall, W. R., Parnell, J. A., & Spillan, J. E. (2013). Stage Collapse at the Indiana State Fair. In Crisis management: Leading in the new strategy landscape (2nd ed., pp. 248-253). Los Angeles: SAGE Publications, Inc. ISBN: 9781412991681.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Industrial safety -- Management -- Case studies